Religious architecture and Roman expansion: temples, terracottas, and the shaping of identity, 3rd-1st c. BCE - Crawford-Brown, Sophie (Cambridge University Press, 2025)
Religious Architecture and Roman Expansion uses architectural terracottas as a lens for examining the changing landscape of central Italy during the period of Roman military expansion, and for asking how local communities reacted to this new political reality. It emphasizes the role of local networks and exchange in the creation of communal identity, as well as the power of visual expression in the formulation and promotion of local history. Through detailed analyses of temple terracottas, Sophie Crawford-Brown sheds new light on 'Romanization' and colonization processes between the 3rd and 1st centuries BCE. She investigates the interactions between colonies and indigenous communities, asking why conquerors might visually emulate the conquered, and what this can mean for power relations in colonial situations. Finally, Crawford-Brown explores the role of objects in creating cultural memory and the intensity of our need for collective history-even when that 'history' has been largely invented.